2009
DOI: 10.1063/1.3064123
|View full text |Cite
|
Sign up to set email alerts
|

Couette and Poiseuille microflows: Analytical solutions for regularized 13-moment equations

Abstract: The regularized 13-moment equations for rarefied gas flows are considered for planar microchannel flows. The governing equations and corresponding kinetic boundary conditions are partly linearized, such that analytical solutions become feasible. The nonlinear terms include contributions of the shear stress and shear rate, which describe the coupling between velocity and temperature fields. Solutions for Couette and force-driven Poiseuille flows show good agreement with direct simulation Monte Carlo data. Typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 45 publications
2
92
0
Order By: Relevance
“…the flow direction is parallel to the plates. Due to the presence of this force, this Poiseuille flow is more interesting than Couette or Fourier flows, as it presents a bi-modal temperature profile that the NSF equations fail to predict even qualitatively [20,[23][24][25][26]. To assess the modeling accuracy of the ES-BGK equation, g x ¼ 0:22 and 1 (which are also close to the values used in previous BGK simulations [20] and DSMC simulations [23]) are chosen in the following simulations.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…the flow direction is parallel to the plates. Due to the presence of this force, this Poiseuille flow is more interesting than Couette or Fourier flows, as it presents a bi-modal temperature profile that the NSF equations fail to predict even qualitatively [20,[23][24][25][26]. To assess the modeling accuracy of the ES-BGK equation, g x ¼ 0:22 and 1 (which are also close to the values used in previous BGK simulations [20] and DSMC simulations [23]) are chosen in the following simulations.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…These terms are assumed to be zero in the Grad's formulation. The closure equations for these terms in the R13 formulation are (Taheri et al 2009): …”
Section: Derivation and Resultsmentioning
confidence: 99%
“…The R13 equations have also shown good predictive capabilities in high-speed flows (Torrilhon & Struchtrup 2004). Only recently, a set of boundary conditions for the R13 equations has been provided (Struchtrup & Torrilhon 2007;, and it was shown that the equations can also predict Knudsen layer dominated problems to some extent Taheri et al 2009 solver. The error this introduces is acceptable for switching purposes, as an estimate of the local Knudsen number is sufficient.…”
Section: Local Knudsen Numbers Based On the R13 Equationsmentioning
confidence: 99%